Selected Aspects of the Antibacterial Use of Lactic Acid in Food Processing - Dragica Đurđević-Milošević; Andrijana Petrović; Vesna Kalaba; Milka Stijepić; Gordana Jovanović (Engineering Proceedings)
L(+)-lactic acid is authorized as an active substance for biocidal products, with applications in veterinary hygiene, food, and animal feed. Several factors can influence the antimicrobial effect of lactic acid, including the applied concentration of lactic acid, the contact time, and the organic soiling of the surface to which it was applied. The aim of this study was to evaluate the bactericidal activity of 5% (v/v) and 1% (v/v) lactic acid solutions on test bacteria: the Gram-negative strain Salmonella enterica subsp. enterica serovar Typhimurium (ATCC 14028) and the Gram-positive Staphylococcus aureus subsp. aureus (ATCC 33592), which is a strain that is resistant to gentamicin and methicillin (MRSA). A dilution–neutralisation method was used, based on a quantitative suspension test EN 1276, for the evaluation of the bactericidal activity of chemical disinfectants and antiseptics used in food, industrial, domestic, and institutional areas, with the bacterial activity being modified in part of the obligatory test organisms. The obtained results showed no difference in the results of the tests under simulated clean and dirty conditions. Both tested lactic acid concentrations showed a 5 lg reduction in Salmonella Typhimurium. For the tested strain, Staphylococcus aureus (MRSA), the required reduction of 5 lg was not achieved. These results contribute to a better understanding and rationale for the use of lactic acid for antibacterial purposes.